Allelopathic potential of the extracts of non-galled stems and globoid stem galls of Eremanthus erythropappus (DC) McLeish (Asteraceae). (February 2022) - Jorge, Nina de Castro; Guedes, Lubia M.; Aguilera, Narciso; Becerra, José; Isaias, Rosy Mary dos Santos
Abstract: Eremanthus erythropappus (DC) McLeisch (Asteraceae), commonly known as " candeia ", is a native species of Minas Gerais state, Brazil, frequently used in medicine as an anti-inflammatory and antimicrobial agent. Eremanthus erythropappus hosts six different gall morphotypes, whose associated inducers manipulate plant cells and tissues and stimulate the neo-synthesis, maintenance, or inhibition of both primary and secondary metabolites on their host plant organs. Based on the premise that galls can potentialize the chemical composition of their associated host plants, our study investigated the allelopathic potential of methanolic extracts of E. erythropappus non-galled stems and globoid stem galls on Lactuca sativa seeds. We also studied the anatomical alterations induced on lettuce plantlets submitted to the methanolic extracts to describe diagnostic features related to the allelopathic effect. Five pentacyclic triterpenes constituted the major class of the identified compounds, followed by volatile oils, alkane hydrocarbons, alkanes, and ketones. The germination rates were statistically different between the treatments, and among the treatments, and the controls (water and methanol). The pentacyclic triterpenes of the extracts of the non-galled stems and the stem galls have a powerful allelopathic effect on the germination of L. sativa ; a higher effect than that of the sesquiterpenes of the essential oils previously described for the leaf chemical compounds. The galling Neolasioptera sp. activity on E. erythropappus stems elicited the synthesis and accumulation of new chemical compounds, two triterpenes (ɤ-taraxasterol, and β-amyrone) and one alkane (tricosane), and inhibited the synthesis of compounds previously related to extracts of E. erythropappus stems, i.e., two triterpenes (A-neooleana-3(5), 12-diene, and lupenone) and one ketone (2(1H)naphthalenone). These extracts altered the differentiation of root parenchyma cells of L. sativa germinated plantlets, but our premise was not corroborated as the galling activity did not potentialize the allelopathic effects. Highlights: The galling activity culminates in synthesis or inhibition of chemical compounds. The pentacyclic triterpenes of Eremanthus erythropappus have an allelopathic effect. Methanolic extracts of Eremanthus erythropappus altered the root parenchyma cells.